Preparation of a Novel ACS/CS/EDTA Composite from Sugarcane Bagasse for Enhanced Adsorption of Carbon Dioxide - Pham, Quang Minh; Nghiem, Xuan Son; Minh, Thang Le; Vu, Anh-Tuan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
This study presents a simple method for the production of activated carbon (ACS) from sugarcane bagasse. To increase the CO2 adsorption efficiency, the ACS/CS/EDTA composite was prepared by modifying ACS with ethylenediaminetetraacetic acid (EDTA) and chitosan (CS). The as-prepared materials were characterized by X-ray Diffraction (XRD), Field Emission Scanning Electron Microscope (FE-SEM), Energy Dispersive X-ray Spectroscopy (EDS), High Resolution – Transmission Electron Microscope (HR-TEM), Fourier Transform Infra-Red (FT-IR), and N2 adsorption/desorption isotherms. The obtained ACS is an amorphous and porous material and contains both micropores and mesopores. The micropore volume, mesopore volume, Brunauer–Emmett–Teller (BET) surface area and average pore width of the ACS are 0.112 cm3/g, 0.193 cm3/g, 354.8 m2/g and 55.7 Å, respectively. The dispersion of EDTA and CS on the activated carbon leads to a deterioration of the structural properties while it increases the aggregation of the ACS/CS/EDTA composite. The performance of the materials was evaluated by CO2 adsorption at ambient pressure. The effects of EDTA, adsorption temperature and gas composition were also investigated in detail. In addition, the durability of the composite was evaluated through the adsorption and desorption cycle. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).